2021
DOI: 10.1111/brv.12763
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of fungus farming in wood‐boring Coleoptera – a palaeontological perspective

Abstract: Insect-fungus mutualism is one of the better-studied symbiotic interactions in nature. Ambrosia fungi are an ecological assemblage of unrelated fungi that are cultivated by ambrosia beetles in their galleries as obligate food for larvae. Despite recently increased research interest, it remains unclear which ecological factors facilitated the origin of fungus farming, and how it transformed into a symbiotic relationship with obligate dependency. It is clear from phylogenetic analyses that this symbiosis evolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 115 publications
1
11
0
Order By: Relevance
“…Fungus farming in Curculionidae weevils evolved independently at least 13 times in the subfamily Scolytinae and one time in the subfamily Platypodinae ( Jordal and Cognato, 2012 ; Biedermann and Vega, 2020 ). This polyphyletic assemblage of ecologically similar weevils includes ambrosia beetles, derived from phloeomycetophagous bark beetles ( Jordal and Kambestad, 2014 ; Kasson et al, 2016 ; Biedermann and Vega, 2020 ; Peris et al, 2021 ). Bark beetles (Coleoptera: Curculionidae: Scolytinae) are woodborer weevils that breed in the phloem (i.e., inner bark) of woody plants.…”
Section: Plant-degrading Microbial Communities From Insect Fungiculturementioning
confidence: 99%
“…Fungus farming in Curculionidae weevils evolved independently at least 13 times in the subfamily Scolytinae and one time in the subfamily Platypodinae ( Jordal and Cognato, 2012 ; Biedermann and Vega, 2020 ). This polyphyletic assemblage of ecologically similar weevils includes ambrosia beetles, derived from phloeomycetophagous bark beetles ( Jordal and Kambestad, 2014 ; Kasson et al, 2016 ; Biedermann and Vega, 2020 ; Peris et al, 2021 ). Bark beetles (Coleoptera: Curculionidae: Scolytinae) are woodborer weevils that breed in the phloem (i.e., inner bark) of woody plants.…”
Section: Plant-degrading Microbial Communities From Insect Fungiculturementioning
confidence: 99%
“…All known members of the family develop in wood as larvae and mutualism with fungi has been reported for a few species (Batra and Francke-Grosmann 1961;Wheeler 1986;Young 2002;Lawrence 2010;Casari and Albertoni 2013;Toki 2021), although more rigorous study and evidence are needed if the other unstudied lymexylid beetles are strongly connected with fungi (Lawrence 2010). Recently, Peris et al (2021) discussed a potentially crucial role of the lymexylids as wood-boring insects, with a special emphasis on the insect-fungus mutualism, more specifically the cultivate ambrosia fungi and their associations. Moreover, Peris et al (2021) considered that Lymexylidae might actually be one of the ambrosia beetles based on the fact that some of their larvae feed primarily on symbiotic ambrosia fungi in tunnels or caves in woody tissues following the criteria by Kirkendall et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Peris et al (2021) discussed a potentially crucial role of the lymexylids as wood-boring insects, with a special emphasis on the insect-fungus mutualism, more specifically the cultivate ambrosia fungi and their associations. Moreover, Peris et al (2021) considered that Lymexylidae might actually be one of the ambrosia beetles based on the fact that some of their larvae feed primarily on symbiotic ambrosia fungi in tunnels or caves in woody tissues following the criteria by Kirkendall et al (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the extensive production of resin at least in some amber forests was a result of stress (McKellar et al 2011;Seyfullah et al 2018). More precisely, water stress of the resin-producing trees might have been the cause (Martínez-Delclòs et al 2004;Labandeira 2014;Seyfullah et al 2018), possibly mediated by drought, flood diseases, wildfires, or plant parasites (though the impact of plant parasites has been questioned: Peris et al 2016;Peris and Rust 2020; but see also Peris 2020 andPeris et al 2021). Baranov et al (2021) recently reported a large number of hoverfly larvae (Syrphidae) of the group Volucellini preserved in Baltic amber.…”
Section: Introductionmentioning
confidence: 99%